A preliminary firesetting offence chain for adults with intellectual and other developmental disabilities. Issue 2 (3rd April 2023) - Collins, J.; Barnoux, M.; Langdon, P. E.
ABSTRACT: Background: The theoretical understanding of firesetting behaviour has predominantly been developed with men in prisons or psychiatric hospitals without neurodevelopmental disabilities. Consequently, there is a lack of evidence regarding the validity of current theory when applied to adults with intellectual disabilities and/or autism. Method: Thirteen adults in England with intellectual and other developmental disabilities were interviewed about the affective, cognitive, behavioural, and contextual factors leading up to and surrounding a recorded firesetting incident. Interviews were analysed using a Grounded Theory approach. Results: The resulting model consists of four phases: (1) background, (2) early adulthood, (3) pre-offence period, and (4) offence, and post offence period. Conclusion: The model accounts for unique precursors to firesetting including mental health deterioration, poor problem solving, and new motivations for firesetting. Unlike other offence chain theories, the significance of post-offence behaviour and cognitions are highlighted.